Rheological properties of wheat starch influenced by amylose–lysophosphatidylcholine complexation at different gelation phases. (20th May 2015) - Ahmadi-Abhari, S.; Woortman, A.J.J.; Hamer, R.J.; Loos, K.
Highlights: Amylose–LPC complexation was induced at different starch gelation phases. Starch shows different viscosity behaviors due to LPC addition at each gelation phase. Adding LPC after an initial gelation, results in a sharp viscosity peak during cooling. Lower G ′ and G ″ prove the formation of particle gel, resulting in less retrogradation. Abstract: Amylose is able to form helical inclusion complexes with lysophosphatidylcholine (LPC). This complexation influences the functional and rheological properties of wheat starch; however it is well known that the formation of these complexes lead the starchy systems to a slower enzymatic hydrolysis. Based on this, to benefit from both the structuring properties of starch and also lower digestibility of the inclusion complexes, the objective of this study is the formation of amylose–LPC inclusion complexes while developing a firm network providing the desired functional properties in a starchy system. To investigate the influence of amylose–LPC complex formation at different stages of starch gelation on the viscosity behavior of wheat starch, 3% (w/w) LPC was added at three different points of the viscosity profile, obtained by rapid visco analyzer (RVA). LPC addition at all points affected the gelation behavior of wheat starch as compared with the reference. LPC addition at half-peak and peak of the viscosity profile resulted in a viscosity increase during cooling. Measuring the dynamic rheological properties of the freshly prepared gelatinized samples showed a decrease of storage modulus ( G ′) and loss modulus ( G ″) in the presence of LPC. During storage, in the presence of LPC, a lower elasticity was observed which indicates a lower rate of amylose retrogradation due to complexation with LPC.